Relevance of the eastern African coastal forest for early hominin biogeography. Issue 131 (June 2019) - Joordens, Josephine C.A.; Feibel, Craig S.; Vonhof, Hubert B.; Schulp, Anne S.; Kroon, Dick
Abstract: The influence of climate change on hominin evolution is much debated. Two issues hamper our understanding of this process: the limited hominin fossil record, and incomplete knowledge about hominin spatial occupation of Africa. Here, we analyze the presently known hominin fossil distribution pattern and explore the potential geographic distribution of hominins between ∼4.5 and ∼2.5 Ma. We focus on assessing the relevance of the Coastal Forest of Eastern Africa (CFEA) along the Indian Ocean as a core area for early hominin evolution. Based on biogeographic-phylogeographic data we propose the coastal refuge hypothesis: the CFEA provided a refugium for early hominins in periods of variable climate and strong seasonality during eccentricity maxima. From this refuge, evolved species could disperse inland (e.g. to rift basins) via vegetated humid corridors, whenever onset of stable climate periods with low seasonality during eccentricity minima allowed expansion out of the coastal enclave. We develop a conceptual model in time and space, comparing predictions with climatic and hominin fossil records. The results imply that: 1) between ∼4.5 and 3 Ma, ongoing (mostly anagenetic) hominin evolution occurred in the CFEA, punctuated by inland dispersal events at ∼4.4, 4.2, 3.8, 3.5, and 3.2 Ma; 2) before ∼3 Ma, the Afar Basin was a (sub)core area often connected to and relatively similar to the CFEA, while other inland areas were more or less marginal for early hominin habitation; 3) after ∼3 Ma, Northern Hemisphere Glaciation exerted strong influence by causing latitudinal contraction of the CFEA, leading to habitat fragmentation, isolation of hominin populations and possible cladogenetic evolution. A major challenge for the coastal refuge model is the fact that at present, no (hominin) fossils are known from the CFEA. We consider how this can be explained, and possibly overcome with targeted search efforts. Furthermore we discuss how the model can be tested, e.g. with molecular phylogeography approaches, and used to predict new hominin fossil locations. With this study, we hope to contribute a fresh perspective to the climate-evolution debate, emphasizing the role of climatic stability, length of dry season and vegetation cover to facilitate connectivity between hominin core and marginal habitats.